Comparative Study of Lossy and Lossless Image Compression Techniques - N, Karthikeyan; Saravana Kumar N M, Dr; Mugunthan S R3, Dr (International Journal of Engineering and Technology, 2018)
In the current world of computer networks and storage media processing on digital images has been increased. It consumes large volume of bits to process and its storage. To deals with these challenges, compression plays a major role in the data of animage is transmitted through the internet fast and consume sufficient memory for its storage. In this paper, different types of lossless and Lossy image compression techniques are discussed with experimental results. Lossless compression encodes and decodes the data without damaging/no information loss whereas Lossycompression achieves high compression with acceptable loss of information. It services on various applications like military, business, industry, education, social media and application. The reports of their works are compared by applying the standard performance measures of Mean square Error and Peak Signal to Noise Ratio.Â Â